Бібліотеки як інститути національного розвитку українського суспільства в період десталінізації (1953 – 1964 рр.) - Тєвікова, Ольга (Видавництво Львівської політехніки, 2018)
The article reveals the significance of libraries as social institutions in the Ukrainian society in 1953 −1964. Author proves that state ideological control had limited the activity of libraries, and they had formed the appropriate stereotypes of thinking of Ukrainians. At the same time, liberalization has opened up access to information, contributed to change of the soviet thinking. Libraries wasn't an institution of the development of the Ukrainian nation and popularization of Ukrainian culture. But they was contributed to the spread some new phenomena and processes in the society.
Keywords: бібліотека; соціальний інститут; національна пам’ять; лібералізація; книжковий фонд; ідеологічна пропаганда